Digital Transformation of Cartier: Marketing Analysis and Strategic Recommendations - Yu, Nuohan (Transactions on Economics, Business and Management Research, 2024)
The rapid evolution of globalization and shifting market conditions has amplified the importance of innovation within the luxury sector, leading to diverse strategies for growth and development. This research specifically focuses on the digital transformation of Cartier, a renowned luxury jewelry brand, to assess its impact on the company’s growth and success. By analyzing key factors such as market sales, market share, and consumer engagement, the study aims to evaluate how digital transformation has positively influenced Cartier’s performance. Through a detailed examination of current data and documents, the research will not only highlight the successes, but also identify potential challenges or limitations that the brand faces in leveraging digital strategies. Furthermore, the study seeks to propose actionable strategies for accelerating Cartier’s future growth, offering insights into how luxury brands can optimize digital transformation efforts to enhance consumer experiences and strengthen market positions. Ultimately, this paper will provide a comprehensive formula for success in the luxury goods industry, outlining the skills and approaches necessary for brands to thrive in an increasingly digital world. By identifying both the benefits and challenges of digital transformation, this research aims to offer valuable guidance for Cartier and other luxury brands striving for sustainable growth in a competitive global marketplace.